The Effectiveness Of Zoom Application As Online Learning Communication Media For STPK Matauli Students During The Covid-19 Pandemi - Futri Zahrah Handayani Manik; Solihah Titin Sumanti (IHSA Institute, 2022)
The purpose of this study is to determine how effective online learning is when the zoom application is used as a communication medium, how the online learning communication media for STPK Matauli students during the covid-19 pandemic, and how the zoom application is used as a learning communication medium for STPK Matauli students during the covid-19 pandemic. The Matauli Pandan High School of Fisheries and Marine Affairs conducted this study using a qualitative descriptive method. This study included 27 informants, all of whom were students from the 2019-2021 class. Observation, interviews, and document methods were used to collect data. The findings revealed: a) the effectiveness of online learning through the use of the Zoom application as a communication medium for students Matauli Pandan High School of Fisheries and Marine Affairs had 8 students who stated Effective and 19 students who stated Ineffective out of a total of 27 informants from the 2019, 2020, and 2021 classes. b) online learning communication media for STPK Matauli students during the academic year of 2019 Whatsapp, Zoom, and Google Meet are the most popular. According to research conducted in the 2019-2021 class with a total of 27 informants, 13 students used Zoom, 9 students used Whatsapp, and 7 students used Google Meet. c) Students at Matauli Pandan Fisheries and Marine College use Zoom for discussions, presentations, and guidance. According to the findings of research conducted in the 2019-2021 class with a total of 27 informants, 15 students used the Zoom application for discussions, 10 students used it for presentations, and 6 students used it for guidance.